The Influence of the Social Environment Context in Stress and Coping in Sport - Kerdijk, Carlijn; van der Kamp, John; Polman, Remco (Frontiers in Psychology, 2016)
Lazarus (1999) model of stress and coping is based on the reciprocal interaction between the person and the environment. The aim of this study therefore was to examine whether the social environment (significant others) are of influence on the stress and coping of team athletes. The study consisted of two separate studies in which a total of 12 team athletes participated. First, six field hockey players (2 males, 4 females) aged 18-29 years (M = 23.0 years) participated in a diary study. Second, six team athletes of different sports (2 males, 4 females) aged 24-29 years (M = 25.8 years) were interviewed. The results showed that in particular teammates are important for the appraisal of stress and coping in team sports. For over half (i.e., 51.5%) of the reported stressors in the diary study the participants felt that others were of influence on their coping. Team athletes experienced the highest stress intensity during competition, or when they appraised the situation as a threat. When others were of influence the team athletes were most likely to appraise the situation as a challenge and use problem- or emotion-focused coping strategies. These finding might provide a new portal for intervention to enhance coping with stress in sport and enhance performance and satisfaction.